285 Can Measurement of Intravesical Pressure be used for the Diagnosis and Follow up of Necrotizing Enterocolitis?. (October 2012) - Tanriverdi, S; Celik, A; Koroglu, O Altun; Dulger, F; Uygur, O; Yalaz, M; Akisu, M; Kultursay, N
Abstract : Background and Aims: Abdominal compartment syndrome refers to multiorgan failure secondary to increased intraabdominal pressure and circulatory failure. Early diagnosis and treatment of this clinical syndrome resulting with high mortality in children is possible via intravesical pressure (IVP)measurements. Data on IVP is limited in newborns with increased abdominal pressure due to diseases like necrotizing enterocolitis (NEC). We aimed to investigate the predictive value of consecutive IVP measurements for diagnosis and outcome of NEC. Methods: IVP was measured twice daily for 10 days in 61 premature infants below 1500 grams. Measurements of infants with and without NEC were compared. Results: Infants were grouped as; Group 1: without NEC, Group 2: NEC medically treated, Group 3: operated for NEC. Group 1 had lower IVP values compared to infants with NEC (p=0.001). Group 2 and 3 had similiar IVP values (p=0.155). A 10% increase in the consecutive IVP measurements was valuable for predicting NEC. Infants who died due to NEC had higher IVP values compared to surviving infants with NEC (p=0.043). Conclusion: IVP measurements may be helpful for the diagnosis of NEC. Mortality due to NEC in premature infants may also be predicted with high IVP values.